Apparent Metabolisability of Diets Containing Concentrate, Zostera Noltii or Taraxacum Officinalis in Anas Penelope - Fabro, Carla; Fabbro, Matteo Del; Piani, Barbara; Filacorda, Stefano; Susmel, Piero A (Animal Review, 2016)
Four metabolisability trials on captive Wigeons were conducted comparing a complete pelleted diet with others where Taraxacum officinalis and Zostera noltii were added. The daily dry matter (DM) intake of Wigeons varied from 54.4 to 65.5 g/day and the amount of nutrients received from the four diets was similar. The nitrogen (N) content of droppings statistically diminished when Wigeons were fed diets containing Zostera noltii. Correlation among cell wall components (CWC) of droppings and that of intakes was always highly significant and positive. The DM metabolisability of the four diets was 42-51 %. The crude protein (CP) metabolisability varied significantly from 21 % for the diet with Taraxacum to 39 % for that with the Zostera collected in June. The metabolizabilities of CWC also differed significantly among diets. The apparent metabolizabilities of ash with the Zostera diets were significantly higher when compared to those of two other diets.